Answer:
[tex](s + t)(x)= 5x+1[/tex]
[tex](s - t)(x)= -3x-5[/tex]
[tex](s.t)(1) = -7[/tex]
Step-by-step explanation:
Given
[tex]s(x) = x - 2[/tex]
[tex]t(x) = 4x + 3[/tex]
Solving (a): (s + t)(x)
This is calculated as:
[tex](s + t)(x)= s(x) + t(x)[/tex]
[tex](s + t)(x)= x-2 + 4x + 3[/tex]
Collect like terms
[tex](s + t)(x)= x+ 4x-2 + 3[/tex]
[tex](s + t)(x)= 5x+1[/tex]
Solving (b): (s - t)(x)
This is calculated as:
[tex](s - t)(x)= s(x) - t(x)[/tex]
[tex](s - t)(x)= x-2 - 4x - 3[/tex]
Collect like terms
[tex](s - t)(x)= x- 4x-2 - 3[/tex]
[tex](s - t)(x)= -3x-5[/tex]
Solving (b): (s . t)(1)
First, we calculate (s.t)(x)
This is calculated as:
[tex](s.t)(x) = s(x)* t(x)[/tex]
So, we have:
[tex](s.t)(x) = (x - 2) * (4x + 3)[/tex]
Substitute 1 for x
[tex](s.t)(1) = (1 - 2) * (4*1 + 3)[/tex]
[tex](s.t)(1) = - 1 * 7[/tex]
[tex](s.t)(1) = -7[/tex]